Intersectional Analysis of Female Migrants in Indonesia: Case Study of Female Migrant Workers from East Java, 1990-2023 - Awara, Sabina Abelia; Rosalinda, Henny (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study analyzes the experiences of female migrant workers from East Java from 1990-2023 through an intersectionality approach. This study aims to explore the experience of gender-based discrimination, migrant status, and media representation of the condition of female migrant workers. Primary data were collected through semi-structured interviews with 10 returning female migrant workers. The analysis was carried out using a thematic approach with the help of NVivo software. The results show that gender discrimination, non-procedural status, and cultural stereotypes are the main challenges faced by female migrant workers. Within the intersectionality framework, this research found several new aspects based on the interview findings: 4 new aspects in representation intersectionality, 6 new aspects in political intersectionality, and 7 new aspects in structural intersectionality. Existing policies are not yet fully responsive to their specific needs, while non-procedural pathways often increase the risk of exploitation. This study concludes that reforming the migration governance system with a gender perspective is very important to improve the protection and empowerment of female migrant workers.